2009
DOI: 10.1007/s11440-009-0083-6
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction potential of coastal slopes induced by solitary waves

Abstract: Tsunami runup and drawdown can cause liquefaction failure of coastal fine sand slopes due to the generation of high excess pore pressure and the reduction of the effective over burden pressure during the drawdown. The region immediately seaward of the initial shoreline is the most susceptible to tsunami-induced liquefaction failure because the water level drops significantly below the still water level during the set down phase of the drawdown. The objective of this work is to develop and validate a numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…If the tsunami waves broke before inundating, breaking‐wave‐generated turbulence, which is not accounted for here, could have affected the patterns of both turbulence generation and sediment suspension. Furthermore, pore pressure gradient‐induced sediment liquefaction, which can be important during drawdown [ Tonkin et al , 2003; Young et al , 2009], and infiltration of water into the soil onshore are not accounted for. There may also be other processes not yet identified that play an important role during tsunamis owing to the large flow velocities generated.…”
Section: Discussionmentioning
confidence: 99%
“…If the tsunami waves broke before inundating, breaking‐wave‐generated turbulence, which is not accounted for here, could have affected the patterns of both turbulence generation and sediment suspension. Furthermore, pore pressure gradient‐induced sediment liquefaction, which can be important during drawdown [ Tonkin et al , 2003; Young et al , 2009], and infiltration of water into the soil onshore are not accounted for. There may also be other processes not yet identified that play an important role during tsunamis owing to the large flow velocities generated.…”
Section: Discussionmentioning
confidence: 99%
“…Interested reader should refer to (Young et al, 2009a) on this topic. In the present study, the wave loads on the bed are assumed to be small enough and the duration of the loading is short so that the soil behaves linear elastically and no failure model is necessary.…”
Section: Numerical Methods For the Wave-sediment Systemmentioning
confidence: 99%
“…Hence, the responses and failure of coastal slopes due to long wave runup and drawdown were not considered. Young et al (2009a) investigated the influence of solitary wave runup and drawdown on the soil responses using an uncoupled wave-soil model. The wave model was the same as the one presented here, but the sediment transport processes were not considered.…”
Section: Wave-induced Seabed Responsementioning
confidence: 99%
“…It would thus be reasonable to characterize the constitutive response of the soil skeleton with a Mohr-Coulomb plasticity or similar models, since the compression cap is unlikely to be activated particularly when the effective-mean-normal stress decreases further as a result of the loss of suction with increased saturation. A simpler plasticity model such as the Mohr-Coulomb model also requires fewer material parameters than any of the more sophisticated constitutive models available in the literature (see [76]). For the soil at CB1, which is mostly colluvium, laboratory-determined values of friction angle are available [53,54].…”
Section: Introductionmentioning
confidence: 99%